2008
DOI: 10.1111/j.1461-0248.2008.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the evidence for ecological synergies

Abstract: There is increasing concern that multiple drivers of ecological change will interact synergistically to accelerate biodiversity loss. However, the prevalence and magnitude of these interactions remain one of the largest uncertainties in projections of future ecological change. We address this uncertainty by performing a meta-analysis of 112 published factorial experiments that evaluated the impacts of multiple stressors on animal mortality in freshwater, marine and terrestrial communities. We found that, on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
650
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 630 publications
(692 citation statements)
references
References 56 publications
(191 reference statements)
36
650
1
5
Order By: Relevance
“…However, from a basic rather than applied perspective, there is no reason to place primacy on synergism because the percentage of antagonistic interactions, in both drug-drug and ecological-driver effects, is roughly equal to the percentage of synergistic interactions. (In drug studies, 26% were found to be synergistic and 37% antagonistic [35]; in terrestrial systems, 35% synergistic and 42% antagonistic [39]; and in marine systems, 36% synergistic and 38% antagonistic [51]). Moreover, our study suggests that antagonism becomes more frequent than synergism when searching for emergent higher-order interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from a basic rather than applied perspective, there is no reason to place primacy on synergism because the percentage of antagonistic interactions, in both drug-drug and ecological-driver effects, is roughly equal to the percentage of synergistic interactions. (In drug studies, 26% were found to be synergistic and 37% antagonistic [35]; in terrestrial systems, 35% synergistic and 42% antagonistic [39]; and in marine systems, 36% synergistic and 38% antagonistic [51]). Moreover, our study suggests that antagonism becomes more frequent than synergism when searching for emergent higher-order interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies of how multiple predators affect prey population dynamics may provide a strong correspondence because the survival rates of prey species are analogous to the growth rates of bacteria in multiple drug environments (e.g. [39]) and appear in the multiple predator effect (MPE) metrics in the same exact form as in our metrics for net interactions (i.e. the deviation from additivity (DA) measure) below.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary ecological research recognizes the importance of studying the simultaneous impact of multiple drivers of global environmental change [6][7][8][9], and our results suggest that focusing on a single driver will provide only restricted insight into the impacts of global changes on species and their interactions. Here, we found evidence that temperature (using latitude as a surrogate) and the degree of habitat fragmentation (represented simultaneously by proximity to fragment edges and the area of forest fragments) both exerted influences on the density and trophic interactions of all levels of a tri-trophic food chain in New Zealand.…”
Section: Discussionmentioning
confidence: 93%
“…In the wider literature, non-additive impacts of multiple drivers are also considered to dominate studies that have investigated the simultaneous impacts of multiple drivers [2,7]. Although these non-additive interactions are often assumed to be synergistic in nature [11,53], several meta-analyses have found similar numbers of studies displaying antagonistic interactions between drivers [2,7]. In one of these reviews, community-level studies largely exhibited antagonistic interactions, whereas studies at population level largely exhibited synergistic responses [2].…”
Section: (A) Simultaneous Global Environmental Change Driversmentioning
confidence: 99%
See 1 more Smart Citation